Analysis of Supporting Factors for Payment Technology Utilization in MSMEs using Technology Acceptance Model (TAM) Method - Asmara, Maisa Azizah; Nurlia; Sari, Dina Fahma; Asrijal, Andi; Muafiqie, Humaidah (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the factors that influence the adoption of digital payment technology in micro, small and medium enterprises (MSMEs) using the Technology Acceptance Model (TAM) method. This research uses a quantitative approach with a sample of 85 MSMEs in Bandung City that have used QRIS mobile digital payment services. This research uses a quantitative approach with primary data obtained from MSME owners or managers in Bandung City who have used QRIS digital payment services. The results of the analysis show that factors such as perceived ease of use, perceived benefits, and security affect the intention to use QRIS payment technology. In addition, validity, reliability, normality, and multicollinearity tests are also carried out to ensure data reliability and validity. The results of hypothesis testing show that all independent variables, namely Perceive in Use, Perceive in Usefulness and Security in Use, have a significant effect on user behavior in using QRIS. This research contributes to analyzing the acceptance and use of digital payment technology in MSMEs.